2017
DOI: 10.1177/1010428317695025
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of parkin by promoter methylation correlated with lymph node metastasis and genomic instability in nasopharyngeal carcinoma

Abstract: This study aimed to investigate the inactivation of the parkin gene by promoter methylation and its relationship with genome instability in nasopharyngeal carcinoma. Parkin was considered as a tumor suppressor gene in various types of cancers. However, its role in nasopharyngeal carcinoma is unexplored. Genomic instabilities were detected in nasopharyngeal carcinoma tissues by the random amplified polymorphic DNA. The methylation-specific polymerase chain reaction, semi-quantitative reverse transcription polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(90 reference statements)
2
6
0
Order By: Relevance
“…It was demonstrated that cells overexpressing PARK2 had a lower migratory and invasive capacity in vitro . This tumor suppressive phenotype linked to PARK2 expression has been observed previously in different cancer types, including non-small cell lung cancer ( 39 ), breast cancer ( 10 ) and nasopharyngeal carcinoma ( 31 ). Notably, PARK2 deficiency in melanoma cells suppressed migration by inhibiting mitofusin 2 (MFN2) ubiquitination; however, contradictorily, malignant melanoma and metastatic malignant melanoma tissue analyses revealed higher levels of PARK2 and MFN2 ( 40 ).…”
Section: Discussionsupporting
confidence: 74%
“…It was demonstrated that cells overexpressing PARK2 had a lower migratory and invasive capacity in vitro . This tumor suppressive phenotype linked to PARK2 expression has been observed previously in different cancer types, including non-small cell lung cancer ( 39 ), breast cancer ( 10 ) and nasopharyngeal carcinoma ( 31 ). Notably, PARK2 deficiency in melanoma cells suppressed migration by inhibiting mitofusin 2 (MFN2) ubiquitination; however, contradictorily, malignant melanoma and metastatic malignant melanoma tissue analyses revealed higher levels of PARK2 and MFN2 ( 40 ).…”
Section: Discussionsupporting
confidence: 74%
“…Addressing the molecular cause for Parkin loss, next we focused on its promoter methylation. It is reported that the Parkin promoter sequence contains distinct CpG islands that are frequently methylated in other cancers [15, 22]. As far as the authors are aware, we provide the first evidence that promoter methylation is a major event for the Parkin inactivation in breast cancer.…”
Section: Discussionsupporting
confidence: 50%
“…It is an emerging molecular marker which raises the hopes for the development of novel therapeutics in combating cancer [20, 21]. Recent studies have reported aberrant methylation at Parkin promoter among acute lymphoid leukemia (ALL), chronic granulocytic leukemia (CGL) [15], nasopharyngeal carcinoma [22] and cervical cancer [9]. Although the precise genetic and epigenetic mechanisms contributing to Parkin loss in breast cancer remain elusive, this prompted us to investigate the possible mechanisms as well as the potential role of Parkin gene in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis is a major cause of cancer-related death. Parkin expression is significantly lower in tumors with lymph node metastases than in tumors without such metastases in the case of clear-cell renal cell carcinoma [ 56 ], pancreatic cancer and nasopharyngeal carcinoma [ 47 , 57 ]. Work from our laboratory has shown that Parkin is frequently down-regulated in breast cancer, and that lower Parkin expression correlates with worse distant metastasis-free survival [ 24 ].…”
Section: Introductionmentioning
confidence: 99%